Long-Read Sequencing to Unravel Complex Structural Variants of CEP78 Leading to Cone-Rod Dystrophy and Hearing Loss - Ascari, Giulia; Rendtorff, Nanna D.; De Bruyne, Marieke; De Zaeytijd, Julie; Van Lint, Michel; Bauwens, Miriam; Van Heetvelde, Mattias; Arno, Gavin; Jacob, Julie; Creytens, David; Van Dorpe, Jo; Van Laethem, Thalia; et al. (Frontiers in Cell and Developmental Biology, 2021)
Inactivating variants as well as a missense variant in the centrosomal CEP78 gene have been identified in autosomal recessive Cone-Rod Dystrophy with Hearing Loss (CRDHL), a rare syndromic inherited retinal disease distinct from Usher syndrome. Apart from this, a complex structural variant (SV) implicating CEP78 has been reported in CRDHL. Here we aimed to expand the genetic architecture of typical CRDHL by the identification of complex SVs of the CEP78 region and characterization of their underlying mechanisms. Approaches used for the identification of the SVs are shallow whole genome sequencing (sWGS) combined with quantitative PCR and long-range PCR, or ExomeDepth analysis on whole exome sequencing data. Targeted or whole genome nanopore long-read sequencing (LRS) was used to delineate breakpoint junctions at the nucleotide level. For all SVs cases, the effect of the SVs on CEP78 expression was assessed using qPCR on patient-derived RNA. Apart from two novel canonical CEP78 splice variants and a frameshifting single nucleotide variant, two SVs affecting CEP78 were identified in three unrelated individuals with CRDHL: a heterozygous total gene deletion of 235 kb and a partial gene deletion of 15 kb in a heterozygous and homozygous state, respectively. Assessment of the molecular consequences of the SVs on patient’s materials displayed a loss-of-function effect. Delineation and characterization of the 15 kb deletion using targeted LRS revealed the previously described complex CEP78 SV, suggestive for a recurrent genomic rearrangement. A founder haplotype was demonstrated for the latter SV in cases of Belgian and British origin, respectively. The novel 235 kb deletion was delineated using whole genome LRS. Breakpoint analysis showed microhomology and pointed to a replication-based underlying mechanism. Moreover, data mining of bulk and single-cell human and mouse transcriptional datasets, together with CEP78 immunostaining on human retina, linked the CEP78 expression domain with its phenotypic manifestations. Overall, this study supports that the CEP78 locus is prone to distinct SVs and that SV analysis should be considered in a genetic work-up of CRDHL. Finally, it demonstrated the power of sWGS and both targeted and whole genome LRS in identifying and characterizing complex SVs in patients with ocular diseases.